(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The study examined the impact of petroleum subsidy removal on the healthcare sector in Nasarawa State, Nigeria. The broad objective of the study is to investigate the impact of petroleum subsidy removal on public health care delivery in Nasarawa State Nigeria. The study adopted a survey research design, both primary and secondary data were used for the study. The population of 2,520 was used from which the sample size of 345 was determined using Taro Yamane formular. Logistic multiple regression analysis (logit regression model) was employed to examine the relationship between the dependent and independent variables. The result revealed that increased fuel prices have led to higher transportation costs, reduced access to medical services especially in rural areas and a rise in operational expenses for hospitals and clinics. The study also revealed that the positive and significant outcome for patients’ accessibility (p = 0.0026) suggests that as transportation fares rise, patients find it increasingly difficult to visit healthcare facility. Therefore, the study recommended that the federal and state governments introduce targeted subsidies or grants specifically for the health sector to ensure a continuous supply of essential drugs, medical consumables, and equipment in public hospitals despite the rising cost of energy and logistics. It also recommended that the government, in collaboration with local transport unions, implement subsidized transport schemes or mobile health outreach programs in rural and semi-urban areas to improve patient access to health facilities. The study concludes that while subsidy removal may promote long-term fiscal sustainability, its short-term adverse effects on the healthcare sector are significant.